Is Ivermectin Effective in Treating COVID-19? - Yang, Shuangshuang; Shen, Shan; Hou, Ning (Frontiers in Pharmacology, 2022)
The coronavirus disease 2019 was first discovered in December 2019 and subsequently became a global pandemic with serious political, economic and social implications worldwide. We urgently need to find drugs that can be effective against COVID-19. Among the many observational studies, ivermectin has attracted the attention of many countries. Ivermectin is a broad-spectrum antiparasitic drug that also has some antiviral effects. We reviewed studies related to ivermectin for the treatment of COVID-19 over the last two years (2019.12-2022.03) were conducted in search engines such as Pubmed, Web of Science and, EBSCO Host. 7 studies showed a lower mortality rate in the ivermectin group than in the control group, 6 studies found that the ivermectin group had a significantly fewer length of hospitalization than the control group, and 8 studies showed better negative RT-PCR responses in the IVM group than in the control group. Our systematic review indicated that ivermectin is maybe effective for mildly to moderately ill patients. There is no clear evidence or guidelines to recommend ivermectin as a therapeutic agent for COVID-19, so physicians should use it with caution in the absence of better alternatives in the clinical setting, and self-medication is not recommended for patients.